Pendekatan Gender Equality dan Social Inclution dalam Pengelolaan Limbah Ternak Berbasis Circular Economy di Kelurahan Lempake - I Putu Gede Didik Widiarta; Nurul Fajrih; Amani Aldiyanti; Anhar Faisal Fanani; Akhmat Rizkuna; Roosena Yusuf; Dinar Anindyasari (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
Livestock waste management in Lempake Subdistrict, Samarinda City, presents a significant challenge in achieving sustainability within the livestock sector, especially in urban areas. Improper livestock waste management can lead to water, air, and soil pollution, negatively affecting health and environmental quality. This community service program aims to optimize livestock waste management by applying Circular Economy (CE) principles to reduce environmental impact by recycling livestock waste into biogas and organic compost. The program involves the Krida Karya Utama Farmers Group as the subject of the service, with the primary goal of enhancing the community’s knowledge and skills in sustainable waste management. The methods used include training, outreach, and the application of Gender Equality and Social Inclusion (GESI) principles to ensure the involvement of women in waste management. The program results show an increase in the farmers’ knowledge and skills, which directly impacts the economic resilience of farming families, especially for women. Additionally, Circular Economy-based waste management can reduce pollution and optimize the use of waste as a valuable resource for the community. Despite challenges related to infrastructure and the community’s understanding of the circular economy, this program has contributed positively to the sustainability of the livestock sector and the socio-economic welfare of the community.